Return to the road of capitalism: Recapitulating the post-socialist urban transition - Berki, Márton (Hungarian Geographical Bulletin, 2014)
Over the course of history, relatively slow and gradual processes of urbanisation are occasionally interrupted by periods of turbulent restructuring. The post-socialist transition is definitely one of the most outstanding examples of these changes, directly affecting the lives of over 300 million people. Within the confines of this succinct theoretical recapitulation, firstly, the relationship between capitalist and socialist urbanisation - as a broader conceptual frame - is presented, followed by the brief summary of the post-socialist transition’s general characteristics. Subsequently, the specificities of the urban structure of socialist and post-socialist cities are subsumed, and finally, different scenarios and development perspectives for post-socialist cities are outlined.